How Sexual Violence Affects the Physical Well-Being of Adolescent Girls: A Case of Kirinya Village, Kiira Municipality - Phionah Kukunda (Uganda Christian University, 2023)
The study was about how sexual violence affects the physical wellbeing of adolescent girls in Kirinya village Kiira municipality. and its objectives were, to explore how sexual violence has affected the physical wellbeing of adolescent girls, To identify how sexual violence has affected the mental wellbeing of the adolescent girls, To find out how victims of sexual violence can be helped to recover from the effected of sexual violence, research methods were quantitative and qualitative techniques ,the findings from the study showed that sexual violence led to post traumatic stress disorder. This was represented whereby 40% of the respondents strongly agreed to the statement while 46.7 % of the respondents agreed to the same statement. Generally, the findings from the study revealed that sexual violence of adolescent’s girls in Kirinya village is a public health problem despite that majority of respondents were aware of sexual violence and their consequences. The findings from the study indicate a variance between the specific objective and the study topic.as it showed a positive correlation between sexual violence and the physical well-being of adolescents. Knowledge on preventive methods is still low. It shows some of factors contribute to high prevalence of sexual violence which have been identified were negative beliefs on the reproductive services, inadequacy of friendly adolescent/teenager sex and reproductive health, culture that hinder parents to talk with the adolescents about sexuality matters. ministries should establishment approach which is more holistic to equipping the adolescent girls with appropriate knowledge on sexuality, access to sexual and reproductive health services rather than traditional coaching approaches that focus upon improving sexual ability, attitudes and norms
This is a dissertation.